Passionate Amateurs Theatre, Communism and Love - Ridout, Nicholas (University of Michigan Press, 2013)
Beginning with Chekhov's Uncle Vanya, Passionate Amateurs tells a new story about modern theater: the story of a romantic attachment to theater's potential to produce surprising experiences of human community. Ridout argues that theater in modern capitalism can help us think afresh about notions of work, time, and freedom.Passionate Amateurs tells a new story about modern theater: the story of a romantic attachment to theater's potential to produce surprising experiences of human community. It begins with one of the first great plays of modern European theater- Chekhov's Uncle Vanya in Moscow- and then crosses the 20th and 21st centuries to look at how its story plays out in Weimar Republic Berlin, in the Paris of the 1960s, and in a spectrum of contemporary performance in Europe and the United States. This is a work of historical materialist theater scholarship, which combines a materialism grounded in a socialist tradition of cultural studies with some of the insights developed in recent years by theorists of affect, and addresses some fundamental questions about the social function and political potential of theater within modern capitalism. Passionate Amateurs argues that theater in modern capitalism can help us think afresh about notions of work, time, and freedom. Its title concept is a theoretical and historical figure, someone whose work in theater is undertaken within capitalism, but motivated by a love that desires something different. In addition to its theoretical originality, it offers a significant new reading of a major Chekhov play, the most sustained scholarly engagement to date with Benjamin's Program for a Proletarian Children's Theatre, the first major consideration of Godard's La chinoise as a "theatrical" work, and the first chapter-length discussion of the work of The Nature Theatre of Oklahoma, an American company rapidly gaining a profile in the European theater scene. Passionate Amateurs contributes to the development of theater and performance studies in a way that moves beyond debates over the differences between theater and performance in order to tell a powerful, historically grounded story about what theater and performance are for in the modern world.“Reading a suggestively diverse set of modern performances, and setting those performances within a clear and well-defined theoretical/critical project, Ridout attempts to use the "passionate amateur" at once the spectator, the scholar, and to some extent the characters in the plays, as a critical category disrupting the otherwise fully commodified communication of leisure products... Passionate Amateurs is wholly original, intellectually and critically stimulating, and certain to develop not only discussion but also to lead to a series of important questions in contemporary theatre and performance studies scholarship.